Experimental assessment of the effects of water quality and PV panel orientation on green hydrogen production - Sahbi Ben Abdelwahed; Mehrez Gassoumi; Fakher Hamdi; Ridha Ennetta (International Journal of Thermofluids)
Efficient green hydrogen production using photovoltaic panels requires careful optimization of key parameters such as solar energy-related parameters, electrolysis parameters, system design and operational factors, and economic and environmental factors. By aligning technical design with site-specific solar resources and operational strategies, the system can achieve high efficiency and cost-effectiveness. The present research work focuses on the production of green hydrogen using a proton exchange membrane electrolyzer coupled with a photovoltaic solar panel. The main objective of this work is to explore the influence on green hydrogen production of the water quality and the PV panel orientation as the key factors that mostly affect its production rate; Two water types, demineralized and distilled, and two PV panel configurations, fixed and variable orientations, have been investigated. The results showed that the PV panel orientation is the most critical parameter that affect the green hydrogen production rate. Indeed, a variable orientation of the PV panel gave an increase in hydrogen production from distilled water, by >45 %, compared to fixed PV panel. Furthermore, the water quality plays a significant role in the green hydrogen production. Distilled water enhanced the hydrogen production rate by >10 % in the case of variable PV panel configuration, compared to demineralized water.